Combining ability of diverse maize inbred lines under Striga infestation in Nigeria and Benin - Yallou, C.; Menkir, A.; Adetimirin, Victor O.; Kling, J. (2007)
Striga hermonthica (Del.) Benth. is a parasitic weed that seriously constrains maize (Zea mays L) production in sub-Saharan Africa. Yield losses from the infestation of S. hermonthica on maize can reach up to 100%. Host plant resistance is the most effective means of control of the weed, but the level of resistance in the presently available sources is not high enough to completely control the weed. Higher levels of resistance have been found in Zea diploperennis lltis, Doebley & Guzman, a wild relative of maize. The objective of this study was to determine the mode of inheritance of resistance to S. hermonthica in five inbred lines derived from Z. mays x Z. diploperennis crosses (Zd lines), one inbred line form TZL Composite 1, and four standard inbred lines. The ten lines were crossed in a diallel fashion and the resulting 45 single-cross hybrids were evaluated under artificial striga infestation at two locations each in Nigeria and Republic of Benin for two years. The results showed that general combining ability (GCA) mean squares were much larger than those for specific combining ability (SCN for grain yield under Striga infestation, Striga damage symptom score, and numbers of emerged Striga plants, indicating that for these traits, additive genetic effects were more important than non-additive effects. Interactions of hybrids with environments (years and locations) were significant for three traits. The Zd inbred lines had positive GCA values for grain yield and negative values for Striga damage symptom score, and numbers of emerged Striga plants, On the other hand the standard inbred lines, which were susceptible, had negative GCA values for grain yield and positive values for Striga damage symptom, score and number of emerged Striga plants, Inbred Zd 551 Was the most Striga –resistant line in the study. This line as well as other Zd lines may represent better sources of resistance to Striga than the standard inbred lines.